SOME FEATURES OF CURATIVE ACTION OF A MILK THISTLE OIL REALIZATION FOR LEVER TOXICAL DAMAGE WITH FORMALINE - V. V. Kozlova; D. A. Konovalov; N. N. Vdovenko-Martynova; I. V. Pshukova; A. A. Kruglaya (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article represents the results of experimental researches of metabolic disorders provoked by subacute formalin injection to rats and study of possibility for correction of received changes by the saint milk thistle oil by the changes of clinical and biochemical indices of transaminases, creatinine, general protein, general cholesterol, glucose and triglycerides level in blood.